Understanding the catalytic mechanism of calcium compounds for enhancing crystallinity in carbon fiber - Lee, Sora; Choi, Junyoung; Chung, Yong Sik; Kim, Jiwoong; Moon, Sookyoung; Lee, Sungho (Elsevier BV, 2024)
Graphitized carbon fibers are attractive materials because of their high tensile modulus and thermal and electrical conductivities. These attributes derive from their crystalline structures that develop during heat treatments of up to 3000 degrees C. Despite the costly thermal processes, there is a structural limit for achieving these sought-after properties for polyacrylonitrile-based carbon fibers. Herein, the preparation of polyacrylonitrile-based carbon fibers with highly developed microstructures via calcium-assisted thermal treatments of up to 2700 degrees C is reported. Carbon fibers hydrothermally immersed in a solution of calcium carbonate were heat-treated and their chemical structures traced to investigate the calcium-assisted catalytic graphitization mechanism. Graphitic structures appeared at 1400 degrees C, accompanied by intermediate complexes of carbon and calcium on the carbon fibers surfaces. Further heat treatment of the calcium compounds at 1600 degrees C to incorporate carbon fibers resulted in an interlayer spacing of 0.3360 nm, which was unachievable solely through heat treatment at 2700 degrees C. In addition, the achieved tensile modulus and electrical conductivity of 480 GPa and 1.7 x 103 S/cm, respectively, were significantly higher than those of pure carbon fibers. The calcium ions penetrating the internal structure of the carbon fibers aligned the non-uniform graphene structure and developed the graphite structure of the carbon fibers by acting as catalysts, even at low temperatures.